Analisis Getaran pada Screw Compressor Akibat Pengaruh Putaran Rotor - Sangian, Hadrianus; Rahman, Deni Arif; Rudiwanto, Rudiwanto; Subekti, Subekti; Hamid, Abdul (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
The air compressor engine is becoming a requirement for both large and small industries production machines instead of the drive system of the driven motor becomes pneumatic. In a pneumatic drive system requires certain air pressures are adjusted to the needs of the industry. Compressor engine which widely used is a screw compressor. On the screw compressor, male and female rotors in the air producer are part of the very important because as the primary producer of compressed air from the motor rotation, then the maintenance must be considered regularly, especially vibrations resulting. The study was conducted to test the amount of vibration that occurs on the screw compressor rotor from the rotor rotation variations using vibration measuring devices FFT analyzer. Measurements are made by attaching the accelerometer sensor to the x, y, and z-axis of the compressor screw rotor casing. Three variations rotors are 2557 rpm, 5042 rpm, and 7508 rpm to get a reference to the magnitude of rotation that is best used in the refrigeration machine is reviewed of the amount of vibration produced. From the results of testing and data collection, it can be concluded that vibration is measured using an FFT analyzer of vibration values the highest is at 7508 rpm which is 7.768 Hz and the lowest is at rotation 2557 rpm of 6,442 Hz. Characteristics of screw compressor vibrations in various rotation conditions can be unbalanced due to the emergence of amplitude at 1x rpm it also experiences a misalignment due to generating vibrations which are higher than usual 2x rpm.Â